FEATURES OF ULTRAMICROSCOPIC STRUCTURES OF THE SPLEEN IN MARSH AND POOL FROGS - Dunayevska, O.F.; Goralskyi, L.P.; Stechenko, L.O.; Kolesnik, N.L.; Кривошеєва, О.І. (World of Medicine and Biology, 2018)
Ecological studies of the environment are important to discover not only the degree and intensity of the impact of pollutants but also to follow the dynamics of degradation of ecosystems in time and space. The method of bioindication successfully using for integral evaluation. The marsh frog is responsible all requirements, which correspond for bioindicators. There is information about using other types of frogs in biomonitoring. The spleen is well suited as a bioindicator because it is sensitive to changes in the internal and external environment. The purpose of the study: ultramicroscopic research of the features of the spleen of lake and marsh frogs. The obtained results will allow better selecting the bioindicator and will be used to ensure for environmentally friendly and safe food products, in particular, on fish farms. The selection of spleens was carried out, for the study, in the mature marsh (Pelophylax ridibundus) and pool frogs (Pelophylax lessonae) of both sexes (the ratio female: males was 1: 1) in the morphofunctional phase of the maturity of the organ (age 2-3 years). The frogs were selected in the Ruzhinsky district of Zhytomyr region on the territory of "Zhytomyr fish farm", which has 15 reservoirs. The material was fixed with 2,5 % glutaric aldehyde solution on phosphate buffer with additional fixation in 1 % solution osmium oxide for Coldfield. Then the material was dehydrated in alcohols and acetone, poured into a mixture of epon-araldit. The ultra-thin slices were contrasted with 2 % solution of uranyl acetate and lead citrate. The samples were investigated on an electron microscope of PEM-125K with magnitudes in 4-20 thousand times. The lymphoblasts (without large pronounced nucleoli) are situated in the white pulp of the spleen in marsh frog. Neutrophil granulocytes have had round or oval shape. The cytoplasmic matrix was moderate electron-cavity, it contained organelles. Neutrophils were characterized by a large number of granules. The primary and secondary granules were contoured well in neutrophils. The macrophages contain a large number of primary lysosomes without activated enzymes. Light microscopy and morphometry show no differences in the histostructure of the spleen of the marsh frog and pool frog. It is important to find out at the ultramicroscopic level the selection of bioindicators in environmental biomonitoring. The features of histostructure play special role to ensure the production of ecologically clean and safe food products on the territory of fish farms. Functionally active and inactive neutrophilic granulocytes have been detected in the white and red pulp of the frog`s spleen. The cells, which specific to the spleen and components identified: macrophages, erythrocytes, eosinophils, blood and lymph capillaries etcetera. The fatty inclusions were in the pool frogs, the number of which correlated with an increase in tubules of a non-granular endoplasmic reticulum. We suggest using the pool frog and marsh frog as bioindicators of geosystems.